Peran Motivasi, Budaya dan Lingkungan Terhadap Kinerja: Pada Unit Kerja Sekda Kab. Serang - Fava Fauziah; Septian Hernawan; Endiana Rahman; John Chaidir; Dian Wirtadipura (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The background of this study is the importance of performance improvement efforts in supporting the effectiveness of regional government administration, where performance is not only influenced by individuals but also by organizational factors. The purpose of this study is to discuss the analysis of the role of motivation, work culture, and work environment variables for improving the performance of civil servants at the Serang Regency Secretariat. The study is based on a quantitative approach through an explanatory survey. A total of 140 employees were surveyed using the Slovin 5% method, resulting in 104 samples. Data collection was carried out using a Likert scale questionnaire and analyzed using linear regression. This study shows that motivation, culture, and work environment, through partial and simultaneous effects, have a positive and significant impact on performance. The KD output was 0.474, meaning that 47.4% of the performance variables were influenced by the three variables. These findings indicate that performance can be improved through motivation, internalization of a positive work culture, and the creation of a conducive work environment. This study has theoretical implications for developing human resources in the public sector and practical implications for policymakers in improving the performance of government officials.